The difference of Natural Killer cell activities of the people live in the aircraft noise area of Adi Soemarmo Airport Boyolali, Surakarta, Indonesia - Hartono Hartono (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2011)
Exposure to noises contributes to a health risk. There is sufficient scientific evidence that noise exposure couldinduce hearing impairment, hypertension and ischemic heart disease, annoyance, sleep disturbances, and decreasedschool performance. Other evidence as changes in the immune system and birth defects is limited. The aims of thisstudy is to find out the difference of Natural Killer (NK) cell activities of the people live in the aircraft noise area ofAdi Sumarmo Airport, Boyolali, Surakarta, Indonesia. The research design was an analytical with a cross sectionalapproach, taking location at the Dibal and Gagak Sipat Villages, Ngemplak Sub district, Boyolali District. The studywas conducted from June 2008 to June 2009. The number of subjects involved was 39. They were divided into 3groups. Group 1 was exposed to 52.17 dB of noise level (13 respondents). Group 2 was exposed to 71.79 dB ofnoise level (13 respondents), and Group 3was exposed to 92.29 dB of noise level (13 respondents). The cytotoxicitiesof NK cells was measured by flowcytometric and using a non-radioactive method. The samples were taken using asimple random sampling. The data were analyzed by Anova followed by Post Hoc Test using LSD test completedwith Homogenous Subsets. The results showed that the activity of NK cells of Group 1, 2 and 3 were 12.50 +3.25%,17.20 3.06%, and 22.33 6.30 %, respectively. The Anova test showed that there was a significantdifference of NK cell activities, in the groups of respondents (p =0.000). In conclusion, there was a significantdifference of the NK cell activities of the people live in the aircraft noise area of Adi Sumarmo Airport, Boyolali,Surakarta, Indonesia.Key words : noise-immune system-flowcytometric-blood mononuclear cells-health risk